Understanding Autism : Parents, Doctors, and the History of a Disorder - Silverman, Chloe (Princeton University Press, 2012)
"Autism has attracted a great deal of attention in recent years, thanks to dramatically increasing rates of diagnosis, extensive organizational mobilization, journalistic coverage, biomedical research, and clinical innovation. Understanding Autism, a social history of the expanding diagnostic category of this contested illness, takes a close look at the role of emotion--specifically, of parental love--in the intense and passionate work of biomedical communities investigating autism. Chloe Silverman tracks developments in autism theory and practice over the past half-century and shows how an understanding of autism has been constituted and stabilized through vital efforts of schools, gene banks, professional associations, government committees, parent networks, and treatment conferences. She examines the love and labor of parents, who play a role in developing--in conjunction with medical experts--new forms of treatment and therapy for their children. While biomedical knowledge is dispersed through an emotionally neutral, technical language that separates experts from laypeople, parental advocacy and activism call these distinctions into question. Silverman reveals how parental care has been a constant driver in the volatile field of autism research and treatment, and has served as an inspiration for scientific change"--Provided by publisher.